Wasser als Ware: Die Privatisierung de:r Wasserversorgung in Großbritannien - Guy, Simon; Marvin, Simon (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
Privatisation of British water services has dramatically reconfigurcd both production and consumption intercsts. While critics such as John Ernst decry a growing service inequity, PeterSaunders and Colin Harris celebrate enhanced consumer benefits. Closer investigation of new styles of utility network management reveal spatially complex patterns of social, econornic and environmental change. While worries over the social and public health implications of water poverly grow, the environrnental dividends of privatised water supply become clearer. The paper identifies two recently emcrging logics of networks management; the first prioritises thc shaping of demand over the expansion of supply capacity; the second prioritises the recovery of water charges over the social am! health needs of low income households. These logics highlight powerful resonanccs and dissonances between the economic and environmental bencfits of the commodification process and the social and health costs associated with a sharpening polarisation in access to basic water services.